The psychophysiologic stress and salivary cortisol and alpha-amylase awakening responses to cross-country running competitions in national-level female athletes - Aydemir, M.; Makaraci, Y.; Avci, B.; Ürkmez, Y. C.; Cintineo, H. P. (The Journal of Strength and Conditioning Research, 2025)
Cross-country running, characterized by diverse terrains and environmental conditions, primarily emphasizes individual performance, though team-oriented strategies are also used. This study aimed to examine psychophysiologic stress, anxiety, and race performance of elite female athletes during national cross-country running competitions. Twelve elite-level female cross-country runners were recruited to undergo psychophysiologic state using salivary cortisol and alpha-amylase levels (pre- and postrace) across 2 consecutive rounds of varying difficulty and significance (round 1 and final round). In addition, cortisol and alpha-amylase awakening responses (CAR and AAAR), and state anxiety (State and Trait Anxiety Inventory-I) were assessed on both precompetition and competition days during each round. The findings revealed significant increases in precompetition day AAAR, pre- and postrace cortisol, and postrace alpha-amylase levels in the final round compared with those in round 1 (p < 0.05). Mean race time was also faster in the final round than in round 1 (p < 0.05). Pre- and postrace cortisol levels were correlated with race time in round 1 (r = 0.554; r = 0.594), but not in the final round (p > 0.05). Increased cortisol emerged as a potential indicator of race difficulty and predictors of success in cross-country running. Coaches and athletes may benefit from monitoring cortisol levels to optimize performance during competitions with fluctuating conditions. Further research using saliva analysis as a noninvasive tool for assessing psychophysiologic parameters surrounding competition is warranted in larger samples across various endurance sports, though the data presented here provide a unique view of these responses.